2021
DOI: 10.3390/ma14175035
|View full text |Cite
|
Sign up to set email alerts
|

Technological Characterization of PET—Polyethylene Terephthalate—Added Soil-Cement Bricks

Abstract: The ever-growing consumption and improper disposal of non-biodegradable plastic wastes is bringing worrisome perspectives on the lack of suitable environmentally correct solutions. Consequently, an increasing interest in the circular economy and sustainable techniques is being raised regarding the management of these wastes. The present work proposes an eco-friendly solution for the huge amount of discarded polyethylene terephthalate (PET) wastes by addition into soil-cement bricks. Room temperature molded 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The low results obtained may be associated with the fact that the water did not react properly with the cement grains due to the reduced amount of water needed during the curing process [36,38].…”
Section: Compression Strengthmentioning
confidence: 97%
See 1 more Smart Citation
“…The low results obtained may be associated with the fact that the water did not react properly with the cement grains due to the reduced amount of water needed during the curing process [36,38].…”
Section: Compression Strengthmentioning
confidence: 97%
“…None of the samples reached the average value determined by NBR 8492 [30], which recommends an average value of 2.0 MPa or an individual value of at least 1.7 MPa for compressive strength. This may have been due to the curing process used, that is, ambient curing [36], which hampered the cement hydration process, since it is directly linked to the type of curing used in the production of soil-cement bricks [37].…”
Section: Compression Strengthmentioning
confidence: 99%
“…This makes it difficult to use the material at high levels. Campanhão et al [ 8 ] and Silva et al [ 80 ] evaluated the use of PET waste as RA replacing NA in cementitious materials. The authors evaluated the substitution of up to 30% and observed that the use of the residue causes a reduction in the workability and a decrease in the mechanical strength of the material.…”
Section: Ra From Other Wastesmentioning
confidence: 99%
“…The soil's soaked California bearing capacity (CBR) was also enhanced by utilizing the CKD in clay soil to utilize it as a flexible pavement subgrade [13]. Another application of using soil as a construction material, Tulane et al [14] determined that sandy clay soil is ideal for making soil-cement bricks due to its particle dispersion and sand properties. After modifying the physical properties of the soil by combining it with sand to stabilize its contents, enabling its pressing process [15].…”
Section: Soil Classification CLmentioning
confidence: 99%